Letter from Campbell Morfit to James Curtis Booth, June 24, 1852 - Morfit, Campbell (1852)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes to Booth to discuss matters relating to his work and mentions the sale of his horse, Fanny.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897